Human papillomavirus type 7 identified in digitated warts on facial seborrhoeic eczema of a non‐butcher immunocompetent individual - Yuko Izumi; Masaaki Kawase; Kiyofumi Egawa (Skin Health and Disease, 2023)
Abstract Human papillomavirus type 7 (HPV7) is frequently found in butchers' warts and has been demonstrated in several warts of immunocompromised hosts. HPV7 is rarely identified in non‐butchers' warts, especially in individuals with normal immune status. We describe the first case of multiple HPV7‐induced digitated warts which were developed on the face of a 68‐year‐old Japanese man, whose immune status was normal and who had no history of meat handling. Interestingly, the warts were developed exclusively on the skin affected with seborrhoeic eczema in the face, suggesting that some biologically active factors associated with seborrhoeic eczema and anatomical factors of sun‐exposed facial skin might contribute to the development of HPV7‐induced warts.